High‐speed atomic force microscopy: Imaging and force spectroscopy. Issue 19 (14th June 2014) - Eghiaian, Frédéric; Rico, Felix; Colom, Adai; Casuso, Ignacio; Scheuring, Simon
Abstract : Atomic force microscopy (AFM) is the type of scanning probe microscopy that is probably best adapted for imaging biological samples in physiological conditions with submolecular lateral and vertical resolution. In addition, AFM is a method of choice to study the mechanical unfolding of proteins or for cellular force spectroscopy. In spite of 28 years of successful use in biological sciences, AFM is far from enjoying the same popularity as electron and fluorescence microscopy. The advent of high‐speed atomic force microscopy (HS‐AFM), about 10 years ago, has provided unprecedented insights into the dynamics of membrane proteins and molecular machines from the single‐molecule to the cellular level. HS‐AFM imaging at nanometer‐resolution and sub‐second frame rate may open novel research fields depicting dynamic events at the single bio‐molecule level. As such, HS‐AFM is complementary to other structural and cellular biology techniques, and hopefully will gain acceptance from researchers from various fields. In this review we describe some of the most recent reports of dynamic bio‐molecular imaging by HS‐AFM, as well as the advent of high‐speed force spectroscopy (HS‐FS) for single protein unfolding.